COMPARATIVE CHARACTERISTICS OF PORPHYRIN METABOLISM DISTURBANCES ON LEAD AND BENZENE INTOXICATIONSʼ MODELS - Крижна, С.І. (World of Medicine and Biology, 2014)
The paper presents the results of optimal model reproducing the experimental disturbances of porphyrin metabolism in experimental animals. There is established that modeling of chronic alcohol and lead intoxications reliably lead to disturbances of porphyrin metabolism by indexes of intermediate metabolism of porphyrins of rats. Such changes are always accompanied by liver injure due to increasing activity of plasma indicators cytolysis, cholestasis and parenchymal inflammation. To determine the most optimal intermediates of heme synthesis in the brain is the model of lead intoxication by the dose of 0.5 ml/kg daily for 2 weeks.